Proton Beam Therapy for Thymic Carcinoma with Pericardial Involvement - Pierre Loap, MSc; Nathaniel Scher, MD; Farid Goudjil, PhD; Youlia Kirova, MD; Nicolas Girard, MD; Kim I. Cao, MD (International Journal of Particle Therapy, 2020)
Purpose: Thymic malignancies are the most common anterior mediastinal tumors. Advanced thymic carcinoma treatment relies on chemotherapy and definitive radiation therapy when possible. However, pericardial involvement is problematic for radiation therapy treatment planning owing to significant cardiac radiation exposure. We report the first case of definitive proton beam therapy (PBT) for an advanced thymic carcinoma with pericardial invasion. Materials and Methods: We report the case of a 69-year-old patient treated with definitive radiation therapy for a stage IVB thymic carcinoma with pericardial invasion. Mean doses delivered to critical organs at risk were compared between deep inspiration breath-hold (DIBH) volumetric modulated arc therapy (VMAT) and DIBH-PBT. Results: When compared to DIBH-VMAT, DIBH-PBT reduced the mean doses delivered to the heart by 3.72 Gy (19.0% dose reduction), to the right lung by 5.9 Gy (41.7% dose reduction), to the left lung by 3.63 Gy (19.0% dose reduction), and to the esophagus by 3.57 Gy (21.3% dose reduction). Despite an early mediastinal relapse after 3.0 months, our patient is still alive after a 14-month follow-up, without any radiation-induced cardiac adverse events and is undergoing pembrolizumab-based immunotherapy. Conclusion: Proton beam therapy is an option for definitive irradiation of thymic malignancies invading the pericardium; in this situation, PBT reduces doses to the heart and may help to reduce cardiotoxicity when compared with photon techniques.